Passive and Active Surveillance for Ixodes scapularis (Acari: Ixodidae) in Saskatchewan, Canada. Issue 1 (16th October 2019) - Chilton, Neil B; Curry, Philip S; Lindsay, L Robbin; Rochon, Kateryn; Lysyk, Timothy J; Dergousoff, Shaun J
Abstract: Passive and active surveillance for the blacklegged tick, Ixodes scapularis Say, in the Canadian province of Saskatchewan was conducted over a 9-yr period (2009–2017). More than 26, 000 ixodid ticks, representing 10 species, were submitted through passive surveillance. Most (97%) of these were the American dog tick, Dermacentor variabilis (Say). Of the 65 I. scapularis adults submitted, 75% were collected from dogs. Infection rates of Borrelia burgdorferi, Anaplasma phagocytophilum, and Babesia microti in I. scapularis were 12%, 8%, and 0%, respectively. Although the I. scapularis submitted by passive surveillance were collected from five of seven ecoregions in central and southern Saskatchewan, they were most frequent in the Moist Mixed Grassland and Aspen Parklands. In contrast, no I. scapularis were collected from the extensive field sampling conducted at multiple sites in different ecoregions across the province. Hence, there is no evidence of I. scapularis having established a breeding population in Saskatchewan. Nonetheless, continued surveillance for blacklegged ticks is warranted given their important role as a vector of medically and veterinary important pathogens, and because they have recently become established across much of the southern portions of the neighboring province of Manitoba.